Place and Displacement: Towards a Distopological Approach. Issue 1 (1st January 2019) - Olivier, Abraham
ABSTRACT: Most recently, debates on decolonization, transformation, and Africanization raise, again, critical questions about the continuous dominance of the Western practice of philosophy in an African place. Such debates bear particular reference to colonization; however, they are relevant to any place where displacement is an issue and transformation demanded. Yet, the concept of displacement receives surprisingly little attention in these debates or in literature on place. I argue that place and displacement are inherently related, and explore some implications of this relation with regard to the practice of philosophy. My contention is that while displacement is an issue that raises specific challenges to the practice of Western philosophy in an African context, it is in fact a defining feature of philosophy as such in search of its place in the world. In conclusion, I propose what I call a distopological approach towards a philosophical practice that takes seriously its place and inherent relation to displacement.